Simulacro do espontâneo : um estudo das cartas da pasta rosa, de Ana Cristina Cesar - Bittencourt, Josely (2012)
The Pink File Letters are part of the project that produced the book Antigos e soltos: poemas e prosas da pasta rosa, organized by Viviane Bosi. Based on this book I intend to engage in a critical study of Ana Cristina Cesar’s creative literary process by highlighting procedures that make those letters hybrid texts between confession and fiction, and offer a simulation of the usual letter form, staging the characteristic spontaneity of the genre. An initial historical background of the use of correspondence as “writing the self” for the other aims at approaching the role of epistolary arts in promoting literary aesthetic phenomena, since their protean forms engender spaces favorable to fiction. The argumentative axis of this study of Ana Cristina’s letters turn around the notion of “simulacrum of the spontaneous” developed through the concepts of autobiography and self fiction writing as discussed by Leonor Arfuch, Elizabeth Duque-Estrada, Graciela Ravetti and Diana Irene Klinger who, among others, offer critical-theoretical support for this study.